Polarized Discourse in the Egyptian News: Critical Discourse Analysis Perspective - Issa, Mohammed Mahmoud (IAIN Samarinda, 2015)
The aim of this study is to investigate ideological structures of polarized discourse coded in the reports of two online news websites: egyptindependent and ikwanweb . The study focuses on online news reports relating to three interrelated events: the issuing of a constitutional declaration by Egyptian president, the aftermath clashes outside presidential palace and the issuing of the Egyptian draft constitution. The analysis of these reports is conducted within the framework of Critical Discourse Analysis. The features of the ideologies of polarized discourse are traced through: Quotation patterns and Labeling. The study concludes with a discussion of how both websites establish a dichotomy of we versus them. In addition, the reports of each website marginalize the other through what is termed as ' Absent News'.